MENINGKATKAN MINAT BACA ANAK SEKOLAH DASAR MELALUI PORTOFOLIO ASSESMENT (MENUJU GEMAR MEMBACA) - Buasim Buasim (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
Reading interest should be developed as early possible to become a reading habits and later reading will become a need. In developing reading interest for primary school students, the learning environmental, including classroom library and classroom setting plays an important role.